Humanity's law - Teitel, Ruti G. (New York ; Oxford : Oxford University Press, 2011)
Teitel presents an analysis of a recent change in international human-rights law. Offering examples from around the world she argues that post-Cold War history has witnessed a key transformation: the normative emphasis of the international legal order has been shifting from state security to human security.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights; International law; Humanitarian law